2021
DOI: 10.3390/nu13103645
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Restriction and Supplementation on Cognitive Performances and Mood among Young Adults in Baoding, China: A Randomized Controlled Trial (RCT)

Abstract: The brain is approximately 75% water. Therefore, insufficient water intake may affect the cognitive performance of humans. The present study aimed to investigate the effects of water restriction and supplementation on cognitive performances and mood, and the optimum amount of water to alleviate the detrimental effects of dehydration, among young adults. A randomized controlled trial was conducted with 76 young, healthy adults aged 18–23 years old from Baoding, China. After fasting overnight for 12 h, at 8:00 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Previous studies have shown that dehydration, caused by insufficient fluid intake levels, was common among individuals [ 65 ]. Another study conducted on male and female Chinese adults revealed that it was common to identify dehydrated participants [ 66 ]. In this study, water intake levels from food were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that dehydration, caused by insufficient fluid intake levels, was common among individuals [ 65 ]. Another study conducted on male and female Chinese adults revealed that it was common to identify dehydrated participants [ 66 ]. In this study, water intake levels from food were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been observed that the hydration status of the subject at the time of the assessment can affect the results obtained, in terms of body composition [ 57 ]. However, in the present study, the hydration status did not have an effect on the differences found between the skinfold calipers analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…That amount was between 3.86 and 4.5 mL, and it increased due to the impact of artificial light at night [ 31 ]. Some studies have reported that drinking less water increases stress levels [ 62 , 63 ]. In addition, less water consumption may increase the cortisol level in the body and cause it to feel more stressed [ 64 ].…”
Section: Discussionmentioning
confidence: 99%